Teologia Pembebasan: Kajian Peranan Penting Gereja Dalam Memerdekakan Masyarakat Dari Kemiskinan - Martin Luther Manao; Abdon A. Amtiran (Institut Agama Kristen Negeri Toraja, 2021)
This research was conducted to find out how the role of the church in liberating society from poverty. The problem of poverty in the church base areas in Indonesia is a real problem and continues from year to year. Poverty is a human problem. The church as the salt and light of the world is here to make an impact and bring about change. The research uses a qualitative approach by searching literature and field facts to respond to the conditions of poverty and how the church plays a role in liberating people from poverty. The results of the study show the importance of the church's role in bringing change to people who experience poverty. The church can play a role in two things, namely: first, with a political approach, both in terms of realm power and in terms of the good common. Second, the educational approach is to become a facilitator for the community in conducting job skills trainings.